THE BURDEN OF POPULATION AGEING : PUBLIC EXPENDITURES AND THE IMPACT ON ECONOMIC GROWTH - Kiml, Thomas Alexander (2025)
The theoretical part of this thesis focuses on the link between population aging, public spending, and economic growth. It is based on endogenous growth theory, which emphasizes the importance of productive spending on education, infrastructure, and research for long-term growth, and on public choice theory, which explains how political preferences and the demographic structure of voters influence the allocation of public resources. The theoretical part further discusses the results of existing empirical research on the impact of population aging on savings, investment, fiscal sustainability, and macroeconomic performance. The aim is to provide a framework for understanding how demographic changes shape budget priorities and how this allocation in turn affects the dynamics of economic growth. The practical part examines the relationship between population aging and the structure of expenditure and economic growth in European economies. Based on panel data from 1990 to 2023, fixed effects models are used to quantify the impact of population aging. Subsequently, we examine how population aging, in conjunction with selected categories of expenditure (on health, infrastructure, education, and research), affects the rate of economic growth. The practical part confirms that population aging is associated with an increasing share of healthcare spending in GDP, while expenditures on infrastructure, education, and research face negative pressures. The examination of the impact of population aging on economic growth confirms a measurable negative effect on economic growth and, at the same time, its non-monotonic nature.